Persistencia del conducto arterioso en caninos: evaluación retrospectiva de 88 casos (2014 - 2018) - Bökenhans, R. (2019)
Left to right shunting patent ductus arteriosus is one of the most common canine congenital heart defects. It is associated with high mortality. Surgical ligation has been thestandart method of correction. 88 cases have been evaluated in the Veterinary school hospital of the University of Buenos Aires (UBA); 67 were operated on and the results of 32 of the post-surgical patients are presented. One month after surgery a reduction of the fractional shortening (P<0.05) has been observed. Follow-up one year later showed in all controls after surgery a reduction of the left ventricle diastolic diameter (P < 0.01).